(untitled) - Hudnall, Marsha (New York, 1998)
The Truth About Carbohydrates Are carbohydrates fattening? Does sugar make kids hyperactive? Are fiber supplements just as good as the real thing? The questions—and—myths surrounding carbohydrates abound. But with this book, The American Dietetic Association sets the record straight. You will discover: How carbohydrates affect your weight, mood, and physical performance; How fiber helps to reduce the risk for heart disease, diabetes, and other health problems; Why high-protein diets are based on pseudo-science; Why high-carbohydrate, low-fat diets are best for weight loss and weight management; How to get the optimum amount of carbohydrates every day; And much more!
Keywords: Food,Carbohydrates; Carbohydrate content